Capturing CSR: Doing Good Offshore - Davidson, Fay; Wreford, John; Pervan, Graham; Penter, Kevan (Springer, 2014)
Global monitoring, and other drivers of high level reporting standards, have brought increasing pressure to embed Corporate Social Responsibility (CSR) in the day-to-day operations of many multi-national companies. This move toward overt and targeted CSR responses and public reporting is prompting the strategic alignment of CSR with core business. Although driven in part by regulation, CSR initiatives and practice help demonstrate the moral authority of the corporate citizen. Practicing and publicly reporting CSR, presents an organization as ethical and worthy of trust, and in doing so, captures the good will, empathy and trust of stakeholders especially clients, customers and labor, in home countries. The development and maintenance of trust is integral to offshoring success. This research questions how the strategic practice of CSR by organizations, operating global in-house centers (GICs), contributes to relationship management in OBPO by positioning staff in GICs as stakeholders.